Asean Security Community Latar Belakang dan Prospek = ASEAN Security Community Background and Prospect - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The purpose of this research is to provide an explanation about ASEAN Security Community (ASC), background and its prospect. The concept of ASC is originated from Indonesia. ASC, according to Indonesian Government, is envisaged to bring ASEAN's political and security cooperation to a higher plane. The ASC aims at creating a cooperative environment in which conflict is not likely to occur in the first place, and at providing a framework within which disputes will be managed and resolved peacefully. Generally, there are some prominent factors leading Indonesia propose the ASC concept, inter alia: by proposing ASC, Indonesia wants to reconstruct its leader position in ASEAN. The existence of various conflicts among ASEAN's members is the main reason behind the ASC formation. Moreover, the attacks against the United States on 11 September 2001 have pushed ASEAN, particularly Indonesia to strengthen security cooperation of region. The other impetus for this initiative is the dynamics of external powers. Aside from its future, there are also some problems in the forming of an ASC. First, the presence of of various divides within ASEAN. A second problem is the resistance or strong commitment to certain principles of interstate conduct that have served ASEAN so well in the past, but are facing serious challenges.